Doing well by doing good The role of Mexico's firms in achieving sustainable and inclusive growth - Gabriel, Mabel (OECD Publishing, 2017)
The private sector can be a strategic partner in the pursuit of sustainable and inclusive growth, with the ability to have a profound impact, particularly in areas such as climate change, inclusiveness, equality and good governance. Firms could contribute through three different approaches: philanthropic activities not related to the firm's activities through which businesses seek to contribute to improving social and environmental conditions; initiatives related to the firm's operations to diminish their negative impacts and to strengthen those that are positive; and development of innovative products and services. Particularly in the latest two approaches, firms themselves stand to benefit in terms of business opportunities, cost reduction, and consumer loyalty. This paper analyses how Mexican firms perform in terms of environmental, social, and governance practices. The paper provides evidence suggesting that contributing to sustained and inclusive growth brings several financial and productivity advantages to firms. This Working Paper relates to the 2017 OECD Economic Survey of Mexico (www.oecd.org/eco/surveys/economic-survey-mexico.htm)
Keywords: Economics; Mexico